Heritage language Learner Needs, Inclusion and Diversity - Shanthi, Nadarajan; Mary Fatimah, Subet; Dayang Sariah, Abang Suhai (Universiti Malaysia Sarawak (UNIMAS), 2015)
Children learn language from their language experience (1). While much of knowledge is fundamentally non linguistic (2), the concepts have implicit networks of meanings which are formed through the experiences and practice of the external world and, (3) under certain circumstances, the non linguistic knowledge in interwoven into language into the form of explicit knowledge which changes the concept as a whole. For young children, the language the child uses in the classroom must first be sufficiently well developed to enable the child to process the cognitive challenges of the class. [4]. To demonstrate that both L1and L2 learners are capable of developing and achieving at the same pace but need sufficient understanding of the operating language, 40 (5- 7 year olds) were tested for their ability to complete a range of age appropriate linguistic and non linguistic tasks. While most preschool (L1 & L2) completed most age appropriate non linguistic tasks, the L2 learners were unsuccessful with many linguistic tasks. Overall, the study suggest that children are capable of adjusting their views about the environment by as early as six months but to achieve, they need a understanding of the classroom language. The present study provides evidence in support of the use of heritage language and mother tongue for early education.